2010
DOI: 10.1118/1.3471020
|View full text |Cite
|
Sign up to set email alerts
|

Deformable image registration of heterogeneous human lung incorporating the bronchial tree

Abstract: Purpose:To investigate the effect of the bronchial tree on the accuracy of biomechanical-based deformable image registration of human lungs. Methods: Three dimensional finite element models have been developed using four dimensional computed tomography image data of ten lung cancer patients. Each model is built of a body, left and right lungs, tumor, and bronchial trees. Triangular shell elements are used for the bronchial trees while tetrahedral elements are used for other components. Hyperelastic material pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 42 publications
0
44
0
Order By: Relevance
“…We selected lung voxels as uniform material as previous studies showed that the homogeneous model was sufficient to model large scale lung deformation (Al-Mayah et al , 2010; Lai-Fook, 1981). The range of tumor motion magnitude and lung volume change (between end-inspiration and end-expiration) varied among the 8 different patients selected for the study.…”
Section: Discussionmentioning
confidence: 99%
“…We selected lung voxels as uniform material as previous studies showed that the homogeneous model was sufficient to model large scale lung deformation (Al-Mayah et al , 2010; Lai-Fook, 1981). The range of tumor motion magnitude and lung volume change (between end-inspiration and end-expiration) varied among the 8 different patients selected for the study.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Mayah et al (Adil Al-Mayah, Moseley, Velec, Hunter, et al 2010) previously demonstrated that incorporating the vessel tree in the FEM model with its own material properties had little effect on the global deformation. For this reason, the lung was considered in this study as a homogeneous organ and the additional conditions were placed on the closest node in the tetrahedral mesh of the lung.…”
Section: Methodsmentioning
confidence: 99%
“…The intraobserver agreement was 0.930 ± 0.336 mm, similar with other studies. 17 Figure 5 depicts an application example of the selected registration schemes (scheme code: 30) at five representative anatomical levels of the lung. T III.…”
Section: B Performance Evaluation Of Candidate Registration Schemementioning
confidence: 99%